European Outliers? Rethinking Europeanisation and Euroscepticism in Britain and Denmark. Issue 2 (15th March 2021) - Favell, Adrian; Reimer, David
ABSTRACT: In the light of Brexit and ongoing doubts about the future of a united Europe, have Britain and Denmark really been outliers to the collective European project, as suggested by their political positioning towards the EU? Despite the Euroscepticism expressed in referenda and public attitudes, we question whether these two countries are inherently less Europeanised, sociologically speaking, than other member states habitually seen as closer to the European project. Using data from the EUCROSS survey about the transnational practices and identifications of ordinary European citizens in five member states, we show that Britain and Denmark have been positioned close to Germany in terms of the degree and type of European cosmopolitanism and transnationalism found in these countries, and are more transnational societies than Spain and Italy. Moreover, in other ways, Britain and Denmark have been exemplary European societies, embodying the EU's cosmopolitan 'normative power' agenda. We suggest that the marked divide between the 'everyday Europeanisation' of these societies and their political hostility to the EU is a paradox that lies at the heart of the democratic crisis of the continent, a schism that may now be directly corrosive to the longer term cosmopolitanism fostered by European integration.